Spinoza’s Evanescent Self - Sanja Särman (Journal of Modern Philosophy)
Selfhood is a topic of great interest in early modern philosophy. In this essay, I will discuss Spinoza’s radical position on the topic of selfhood. Whereas for Descartes and Leibniz, there is a manifold of thinking substances, for Spinoza, there is, crucially only one: God (1p14; 2p1). Minds, for Spinoza, do not have substantial status, they are instead merely complexes of ideas (2p15), and thus complex modes of the one substance: God. Observations such as these often lead Spinoza’s readers to the conclusion that, whereas for Descartes as for Leibniz, human beings have robust or genuine selves, this is not so for Spinoza. However, this reductionist interpretation is also challenged—in recent times most intriguingly by Koistinen (2009). Koistinen has argued that there are, fundamentally, human selves of whom agency can be predicated in Spinozism. In this paper I discuss to what extent this is true. In section 1, I introduce the reductionist interpretation of selfhood in Spinoza’s thought. In section 2.1, I present and criticize Koistinen’s proposal. In section 2.2, I acknowledge the strength of Koistinen’s view that insofar as human beings act, they are God somehow. In section 3, I propose an alternative reading of human selfhood in terms of witnessing being acted out rather than in terms of being an agent. This view isprima facieparadoxical. In section 4, I nonetheless support it by highlighting that Spinoza seems to have seen practical benefits in knowing oneself to be acted out by God. I conclude the essay by pointing out some comparative directions for future research.